Islamic Republic of Mauritania : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2003)
In this paper, the following statistical data are listed in detail: GDP by sector of origin, growth of output by sector, GDP at current prices, expenditure and savings at current prices, estimated fish catch, composition of fish exports, net production of electricity and water, selected indicators for public enterprises, public utility rates, consumption of petroleum products, unit prices of petroleum products, treasury operations, structure of budgetary revenue, subsidies and transfers, monetary survey, assets and liabilities of central bank, balance of payments, exports, imports, and so on.